A case of adenovirus infection complicated by diffuse alveolar haemorrage in a tourist from Sri Lanka - R. F. Sayfullin; M. A. Sayfullin; N. N. Zvereva; O. E. Ambrosi; V. R. Vengerov; S. K. Pylaeva (Туберкулез и болезни лёгких)
The article describes a rare case of adenovirus infection complicated by diffuse alveolar hemorrhage in a 29 y.o. immunocompetent patient which developed during a trip to Sri Lanka. The course of the disease was accompanied by severe anemia and respiratory insufficiency, etiology of the disease was confirmed by polymerase chain reaction of pharyngeal swabs and sputum sample. After successful supportive treatment, the patient was discharged on the 13th day of hospital stay to continue treatment in the out-patient settings. This case demonstrates the possibility of severe complications in case of adenovirus infection.